Postoperative sexual functioning in total versus subtotal laparoscopic hysterectomy: what do women expect? - Berlit, Sebastian; Hornemann, Amadeus; Sütterlin, Marc; Tuschy, Benjamin (Archives of gynecology and obstetrics, 2017)
PurposeTo evaluate sexual functioning and expected changes in sexual functioning in women with planned total versus subtotal laparoscopic hysterectomy.MethodsA total of 120 women undergoing laparoscopic hysterectomy were preoperatively enrolled in this study with a cross-sectional design. Full data sets were available for 112 patients, so that 56 patients with planned total laparoscopic hysterectomy (TLH) and 56 women with planned laparoscopic supracervical hysterectomy (LASH) were preoperatively assessed. Sexual functioning was evaluated using the female sexual function index (FSFI). Additionally, participants filled in a standardised questionnaire concerning expected changes on sexual function after the procedure. Demographic parameters, expectations concerning postoperative sexuality and FSFI scores were analysed and compared in women undergoing TLH and LASH.ResultsThere were no significant differences concerning demographic parameters and FSFI scores comparing collectives. Sexuality in general was considered more important in women undergoing LASH (2.88 ± 0.83 vs. 2.48 ± 0.89; p = 0.011). Also, in 29 patients (52%) opting for LASH and 8 (14%) patients undergoing TLH a potential change in postoperative sexuality had an impact on their choice for a subtotal/total hysterectomy, respectively (p < 0.001).ConclusionPatients’ expectations concerning preservation of the cervix and postoperative sexuality appear to have the potential to bias investigations comparing total with subtotal hysterectomy. Hence, future research focusing on this issue should be accomplished incorporating patients’ expectations stratified by mode of intervention.
First online: 06 July 2017
Gesehen am 18.06.2018